On the Essential Norm of Multiplications Operators Acting on Cesàro Sequence Spaces. (3rd March 2019) - Ramos-Fernández, Julio C.; Rivera-Sarmiento, María A.; Salas-Brown, Margot
Abstract : In this article, we establish an important property about the growth of sequences in the dual space of Cesàro sequence spaces. As a consequence of this fact, we calculate the measure of noncompactness or the essential norm of the multiplication operatorM u acting on Cesàro sequence spacesc e s p .